2020
DOI: 10.5999/aps.2018.01165
|View full text |Cite
|
Sign up to set email alerts
|

Correction of microtia with constriction features using a superficial temporal fascial flap combined with a rib cartilage graft

Abstract: Background Microtia with constricted features is characterized by a short helical length of variable severity, upper antihelical or scaphal deficiency, and a downfolded upper ear. No consensus has been reached regarding the most appropriate surgical method for this condition. In this study, we aimed to introduce a simple and safe surgical method for the correction or reconstruction of upper helix ear deformities.Methods Between February 2011 and June 2014, eight patients with microtia with constricted upper he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Patients with congenital ear deformities tend to suffer psychological distress manifesting as anxiety, low self-esteem, and behavioral problems [ 12 ]. Traditionally, auricular deformities have been corrected surgically at 6 years of age [ 18 ]. Recently, nonsurgical management by ear molding has emerged as a favorable approach for newborn auricular deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with congenital ear deformities tend to suffer psychological distress manifesting as anxiety, low self-esteem, and behavioral problems [ 12 ]. Traditionally, auricular deformities have been corrected surgically at 6 years of age [ 18 ]. Recently, nonsurgical management by ear molding has emerged as a favorable approach for newborn auricular deformities.…”
Section: Discussionmentioning
confidence: 99%
“…Harvesting the DTF without a sufficient anatomical understanding often causes postoperative complications such as bleeding, facial nerve paralysis, and temporal hollowness [15][16][17][18][19]. Previous studies reported the LTC contained all of the "atrisk" anatomical structures of the temporal area [12,15,20].…”
Section: Discussionmentioning
confidence: 99%
“…Measured dimensions were compared between the reconstructed and normal ear by a few studies, who all reported a difference of less than 10% in each dimension. 35,47,60,84 Audiometrically measured hearing outcomes were reported by three studies, all with improvements of greater than 20 dB. 35,43,56…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Several studies in our review devised and explained their own scoring systems, which in some instances even included the use of multiple independent evaluators. 29,40,47,53,66,88 However, none of these scoring systems were This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%